The Influence of Impulsive Behavior on Financial Management of Online Gamers: A Financial Accounting Perspective - Lutfiah Azzahra; Rahmawati Rahmawati; Rismawati Rismawati (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
This study aims to analyze the influence of risk tolerance, fear of missing out (FOMO), and financial literacy on the impulsive characteristics of gamers. The research method employed is a quantitative approach using a survey technique through questionnaires distributed to active gamer respondents, with a total of 78 responses collected. Data analysis was conducted using Structural Equation Modeling (SEM) approach with the assistance Amos 22 and SPSS 22 to examine the direct relationships among the variables. The results show that risk tolerance and FOMO have a positive influence on gamers' impulsive characteristics, while financial literacy is predicted to have a negative effect. These findings imply that improving financial literacy can serve as a controlling factor against impulsive behavior among gamers, whereas high levels of FOMO and risk tolerance tend to reinforce such tendencies. This research contributes to the understanding of financial aspects in digital economic behavior and psychological, particularly within the online gaming community.